2017
DOI: 10.1515/rjim-2017-0017
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth among women living within 600 meters of high voltage overhead Power Lines: a case-control study

Abstract: Aim. The issue of preterm birth due to exposure to magnetic fields from power lines is unclear. Exposure to electromagnetic field in uterus has been hypothesized as possible preterm birth. The aim of the present study was to determine whether living closer to high voltage power lines increased the risk of preterm labor.Methods. In a nested case-control study, 135 cases of singleton live spontaneous preterm birth in Rohani hospital, Babol, Iran, during the period between 2013 and 2014 were studied. The 150 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In addition, a significant associations was observed between birth defect (adjusted OR = 5.05; 95% Confidence Interval, CI, = 1.52 to 16.78) and living < 600 meters from high voltage power line. No significant risk has shown for newborn death (5). In our resent study raised a question if there is an impact on infertility from high-voltage power lines.…”
mentioning
confidence: 67%
“…In addition, a significant associations was observed between birth defect (adjusted OR = 5.05; 95% Confidence Interval, CI, = 1.52 to 16.78) and living < 600 meters from high voltage power line. No significant risk has shown for newborn death (5). In our resent study raised a question if there is an impact on infertility from high-voltage power lines.…”
mentioning
confidence: 67%
“…Since the offspring can be more easily affected by environmental factors in the prenatal and postnatal periods, exposure to EMF from the embryonic period can cause morphological changes in tissues, decreased fertility, or infertility. Epidemiological studies have shown that there might be a relationship between exposure to EMF and pregnancy problems, such as preterm birth or low birth weight and infertility (Esmailzadeh et al, 2019; Lewis et al, 2016; Sadeghi et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It may also decrease ovarian reserve, which can lead to infertility. [18][19][20][21][22][23] In modern societies, humans are inevitably submerged in a sea of various spectrums of electromagnetic fields. The adverse effects of exposure to electromagnetic fields on human depend on the density of the field and the duration of the exposure.…”
Section: Discussionmentioning
confidence: 99%